Estudo sobre a possibilidade da utilização das técnicas de educação ambiental não formal no contexto escolar - Felipe, Camila Correia Gabeloni (2018)
In view of the environmental problematic and the anthropic impacts the environment suffered, it becomes important to spread practices in Environmental Education on every level of teaching, since they are strategic tools when it comes to changing the collective and individual views, either relating to the Formal environment or the non-Formal one. In this study, it was noted that one type of integration was procured by the intermunicipal public partnerships, through projects, visits to the conservation units, amongst other activities. Thus, six techniques adopted by the CORIPA (Intermunicipal Consortium for the Conservation of the Remaining of the Parana River and its influence area) were chosen for analysis and replication at the Admiral Tamandaré State High School, located at the town of Cruzeiro do Oeste – PR, intending to verify the use of those non-Formal environmental techniques on school context. Starting from the collected information, it was initially defended that the access to scientific knowledge on specific environmental questions could collaborate to reconstruction of a much more enhanced environmental conception. For that, for the collection of data it was adopted the qualitative-quantitative methodology, using documents and theoretical references, workshops and polls (before and after said workshops). For the analysis, the data analysis based on analytical description technique was chosen, with emphasis in the Bardin Content Analysis (1977). Based on the modus operandi of the mentioned techniques, along with the answers listed on the polls and the speech of the participants during the development of the workshops, it was stated that the way the environmental techniques are applied on the non-Formal environment, in whole, are not efficient for the reconstruction of a more enhanced environmental conception (specifically for high school students). In conclusion, the techniques should have their modus operandi adapted to each environment and better time distribution that will remain active, collaborating to the idea of programs, instead of what is done today, which are based on projects.